Designing a Virtual Reality (VR) Storytelling System for Educational Purposes. - Siew, Yung Lau; Chen, Chwen Jen (Springer Netherlands, 2009)
This paper addresses the instructional design of a virtual reality (VR)-based educational storytelling system. Indeed, the importance of storytelling in education has long been recognized. Stories are pervasively used as powerful tools in teaching and learning. Although there are efforts to utilize advanced technology, such as virtual reality (VR), in storytelling, most of the research studies focus on immersive-VR that involve expensive and bulky settings, which eventually limit its feasibility to be ubiquitously used. Thus, this project looks into the potential of non-immersive VR, also known as desktop VR, for educational purposes. This alternative low-cost and affordable VR technology requires only conventional computer settings but is able to present an interactive real-time three-dimensional virtual environment (VE) that the learners can navigate in and interact with. A constructivist instructional design theoretical framework [18] is adopted to construct the VR storytelling system. This storytelling system aims to deliver fire safety knowledge to the targeted learners.